PELAKSANAAN PROSES PEMBELAJARAN GURU PAUD SE-KECAMATAN TANAH PUTIH KABUPATEN ROKAN HILIR - Sari, Rosna; Indarto, Wusono; Puspita, Enda (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : This study aims to determine know the results of the implementation of the learning process early childhood teachers. Total population is the entire early childhood teachers in Se-Kecamatan Tanah Putih Rokan Hilir , as many as 79 people from 17 schools and a sample of 44 teachers. Data collection techniques were used that observation . Data analysis techniques used in this study was the percentage . From the research that has been done, it can be deduced that is seen from the average value of all the aspects -aspek Learning Implementation Process Master ECD se - Tanah Putih Rokan Hilir for teachers graduated from high school or equivalent based on the assessment criteria defined , it can be concluded that the results of the average amount of 89.29 % is included in the category of Very Good . Judging from the average value of all the aspects -aspect Learning Implementation Process Early childhood teachers throughout the District Land White Rokan Hilir for teachers graduate Diploma equivalent to a percentage based on the assessment criteria defined , it can be concluded that the results of the average amount of 87.29 % is included in Very Good . of the average value of all aspects of early childhood Teacher Learning Implementation Process se - Tanah Putih Rokan Hilir for teachers graduate S1 or equivalent Based on the assessment criteria defined , it can be concluded that the results of the average amount of 88.17 % ie included in Very Good .Keywords : Learning Process